Evaluation of Left Atrial Size in Patients with Hypertension with Left Ventricular Hypertrophy in a Tertiary Care Hospital of Nepal (Journal of Invasive and Clinical Cardiology, 2023)
Background: The hypertensive heart disease is characterized by left ventricular hypertrophy (LVH), atrial remodeling and AF. The impact of hypertension on the left atrium is little known. LVH is a link between hypertension and left atrium enlargement (LAE). LAE raises the suspicion of increased BMI, DM, dyslipidemia in hypertension. Thus, the aim of this study is to evaluate the LA size hypertensive patients without metabolic disorder and to evaluate whether there is a relationship between LVH and LAE. Methods: This is a prospective, observational study conducted in SGNHC, Kathmandu, Nepal. Our Study included 91 hypertensive patients fulfilling inclusion criteria from August 2021 to January 2022. Results: 91 patients were enrolled for the study, out of which 50 (54.9%) were males and 41 (45.1%) were females. Mean age of patients was 47.77±12.1 years. 23(25%), 28(31%) and 40 (44%) patients fulfilled SV3+RaVL, SV1+RV5, RaVL criteria respectively of LVH. 10(11%),12 (13%) and 25(27.5%) satisfied the criteria of LVMI, IVSD, RWT respectively. The mean values of LA diameters, area, volume and volume Index were calculated. There were a significant associations between left ventricular internal diameters and age with LAVI (p-value